PENERAPAN MODEL PEMBELAJARAN YURISPRUDENSIAL UNTUK MENINGKATKAN PERCAYA DIRI DAN PRESTASI BELAJAR - Nurlelah; Buyung (UNIB Press, 2024)
This research aims to: (1) describe the application of the jurisprudential learning model to increase self-confidence in Civics subjects of VIII class students, (2) describe the application of the jurisprudential learning model to improve learning achievement in Civics subjects of VIII class students and (3) describes the application of an effective jurisprudential learning model to improve learning achievement in Civics subjects of VIII class students at SMPN 37 OKU. The research design used in this study was Classroom Action Research (CAR) and Quasi Experiments. The research subjects were students of class VIII.C SMPN 37 OKU in the odd semester of the academic year 2022/2023, with the Simple Random Sampling technique obtained quasi-experimental samples were class VIII.B and class VIII.A as the control class. The data collection technique of this research used observation and tests. Data analysis techniques are descriptive statistics and t-test. The results of this study conclude that the application of the jurisprudential learning model can increase self-confidence and learning achievement in Civics subjects of VIII class students at SMPN 37 OKU